2017
DOI: 10.1016/j.jacc.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Coating and Aspirin Nonresponsiveness in Patients With Type 2 Diabetes Mellitus

Abstract: A high proportion of patients treated with EC aspirin failed to achieve complete inhibition of TXB generation due to incomplete absorption. Reduced bioavailability may contribute to "aspirin resistance" in patients with diabetes. (Pharmacodynamic Evaluation of PL2200 Versus Enteric-Coated and Immediate Release Aspirin in Diabetic Patients; NCT01515657).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 25 publications
1
85
0
12
Order By: Relevance
“…In case of aspirin initiation in primary CV prevention, low-dose aspirin (75-100 mg) should be the first choice, with preference for uncoated formulations (among patients treated with enteric coated aspirin, the rate of failure of the complete inhibition of thromboxane B 2 is high due to incomplete absorption 46 ) and concurrent use of proton pump inhibitors for those at high risk for GI bleeding, avoiding the contemporary administration of NSAIDs. Anyway, the balance between aspirin therapy and risk for bleeding is still uncertain in patients with no evidence of CV disease.…”
Section: The Questionmentioning
confidence: 99%
“…In case of aspirin initiation in primary CV prevention, low-dose aspirin (75-100 mg) should be the first choice, with preference for uncoated formulations (among patients treated with enteric coated aspirin, the rate of failure of the complete inhibition of thromboxane B 2 is high due to incomplete absorption 46 ) and concurrent use of proton pump inhibitors for those at high risk for GI bleeding, avoiding the contemporary administration of NSAIDs. Anyway, the balance between aspirin therapy and risk for bleeding is still uncertain in patients with no evidence of CV disease.…”
Section: The Questionmentioning
confidence: 99%
“…Although small proof‐of‐concept studies demonstrated that obese subjects could become fully responsive to aspirin at increased daily doses, as indicated by a significant inhibition of serum thromboxane B2, conflicting results have emerged that doubling the aspirin dose did not lead to further platelet inhibition, suggesting limited improvement in responses to the high aspirin dose . One hundred and fifty milligrams of aspirin was once recommended for obese patients over 120 kg, and more recently, lower nonresponsiveness rate has been demonstrated with 325 mg aspirin among type 2 diabetes . Although poor response to low‐dose aspirin might be common in patients undergoing bariatric surgery, a significant improvement is anticipated as a result of the surgery.…”
Section: Limitationsmentioning
confidence: 99%
“…17,18 One hundred and fifty milligrams of aspirin was once recommended for obese patients over 120 kg, and more recently, lower nonresponsiveness rate has been demonstrated with 325 mg aspirin among type 2 diabetes. 19 Although poor response to low-dose aspirin might be common in patients undergoing bariatric surgery, a significant improvement is anticipated as a result of the surgery. The low-dose aspirin strategy used in this study attempted to reduce dose-dependent adverse effects, particularly after the surgery, and ensure patients to receive standard doses of aspirin.…”
Section: Limitationsmentioning
confidence: 99%
“…There are some readily identifiable reasons why patients demonstrate persistent platelet aggregation despite aspirin treatment. These include use of NSAIDs, poor absorption of enteric coated aspirin formulations, compliance, inadequate dose, gastric bypass surgery, and rate of platelet turnover . This study eliminated these factors as sources of variance in aspirin resistance in this clinical population in order to distinguish between true pharmacokinetic resistance and pharmacodynamic resistance.…”
Section: Discussionmentioning
confidence: 99%